Implementasi Algoritma Mars Pada Penyandian Record Database - Alimah Alimah; Nelly Astuti Hasibuan; Taronisokhi Zebua (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Database records in the form of text are very widely used, so it is very vulnerable to data theft by unauthorized parties. In order to maintain the security of database records, it can be done by using cryptographic techniques. Cryptographic techniques can encode database records by encrypting them in the form of passwords that are not understood. The Mars algorithm is an algorithm that uses a 128-bit key and the encryption process consists of 32 rounds. This symmetry algorithm will produce a higher level of security against the database record because it can encode it into a password with a fairly complex process that will make it difficult for cryptanalysts to access the image. This research uses the Mars Algorithm for the encryption and decryption process, so that in the process it is necessary to go through several long steps in order to produce the final cipher. This research describes the process of securing a database record by encoding it based on the Mars algorithm, in the form of a password that is difficult for others to understand and understand. This is done in an effort to minimize acts of misuse of database records